2015
DOI: 10.1039/c4gc01545b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave, ultrasound and ball mill procedures for bio-waste valorisation

Abstract: Bio-waste valorisation has been one of the hottest research topics worldwide over the last decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…By the centrifugal forces high mass/heat transfer rates are obtained. [158] It has been applied to biomass transformation processes, [159] such as biodiesel synthesis, [160] biomass pyrolysis, [161] and the sugar dehydration to furans (e. g., HMF and furfural). [128,129] Enhanced heat/mass transfer can be also obtained in continuous flow microreactors that consist of reaction channels with diameters on the order of ca.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
“…By the centrifugal forces high mass/heat transfer rates are obtained. [158] It has been applied to biomass transformation processes, [159] such as biodiesel synthesis, [160] biomass pyrolysis, [161] and the sugar dehydration to furans (e. g., HMF and furfural). [128,129] Enhanced heat/mass transfer can be also obtained in continuous flow microreactors that consist of reaction channels with diameters on the order of ca.…”
Section: Process Intensification For Biomass Conversionmentioning
confidence: 99%
“…Recently, mechanochemistry has been widely applied in chemical and material synthesis with the unique advantage of enabling efficient solid-state reactions and the ability to directly convert various recalcitrant feedstocks. [61][62][63][64][65][66][67][68][69][70][71][72][73][74] A series of studies transforming biomass in a solvent-free way have been demonstrated. For example, cellulose was converted to watersoluble oligomers by both mineral acids and solid acids in a ball milling process, 75,76 while lignin was decomposed similarly in the presence of a base.…”
Section: Introductionmentioning
confidence: 99%
“…As alternatives to conventional mineral acids (e.g., H 2 SO 4 and HCl), the hydrolysis of cellulose with solid acid catalysts is perceived to be a more environmentally benign approach as their use simplifies downstream processing . In this context, ILs containing acidic units may potentially dissolve and selectively deconstruct biomass while simultaneously catalyzing reactions .…”
Section: Introductionmentioning
confidence: 94%